Perspectives of Public Pedagogy in Christopher Nolan’s Cinema. Case Studies on Inception and the Dark Knight Rises - Aletras, Christopher Nolan; Mouzaki, D.; Sagri, M.; Gerasaki, S. (European Journal of Multidisciplinary Studies, 2022)
The educational and pedagogical impact of cinema is investigated through two popular Christopher Nolan’s films Inception and The Dark Knight Rises. Analysis of his films, in the context of cinema public pedagogy, shows that Nolan’s way of film-making defines a specific set of challenging and reversing messages, hidden behind the Hollywood mainstream standars. Moreover, throughout this analysis, the power of the public pedagogy of the cinematic medium is established, and cinema is approached as a powerful tool that sets the standards of private and public behavior by combining entertainment and politics, according to [Giroux, 2008]. We end up in suggesting that the public pedagogy of cinema be embedded in the educational system as a distinct educational tool.
Keywords: Public Pedagogy, Giroux